BK Teachers' Strategies in Dealing with the Mental Health of Students Victims of Cyberbullying through Islamic Individual Counseling Services - Betsi Siti Nurhidayah; Alifa S Rahmadhina (P3M STAI Kuningan, 2026)
Background: Cyberbullying is one of the serious problems that affect students' mental health in the digital era. Victims of cyberbullying tend to experience psychological disorders such as anxiety, stress, low self-esteem, and depression.Objectives: This study aims to analyze the strategies of Guidance and Counseling (BK) teachers in dealing with the mental health of students who are victims of cyberbullying through Islamic individual counseling services.Method: The research uses a qualitative approach with a case study method. The data collection technique was carried out through interviews, observations, and documentation of BK teachers and students in one of the secondary schools. The research subjects consisted of one BK teacher and three students who were victims of cyberbullying, with a duration of three months of research. The results of the study show that the strategy of BK teachers is carried out through the identification of students' psychological conditions, the provision of intensive individual counseling services, Islamic spiritual approaches, the provision of religious motivation, and the strengthening of social support from families and schools. Finding and Implication: The Islamic approach is applied through strengthening the value of patience, tawakal, muhasabah, and the reading of Qur'anic verses that are relevant to the emotional condition of students. These strategies can help students reduce anxiety, increase confidence, and improve mental health conditions gradually.Conclusion: This research shows that Islamic individual counseling services can be an effective alternative in handling victims of cyberbullying in the school environment.